A novel MYB transcription factor regulates ascorbic acid synthesis and affects cold tolerance. (16th August 2018) - Xing, Caihua; Liu, Yue; Zhao, Liangyi; Zhang, Shaoling; Huang, Xiaosan
Abstract: Dehydroascorbate reductase (DHAR) plays an important role in stress responses, but the transcriptional regulation of DHAR in response to abiotic stress is still poorly understood. In this study, we isolated a novel R2R3‐type MYB transcription factor from Pyrus betulaefolia by yeast one‐hybrid screening, designated as PbrMYB5 . PbrMYB5 was localized in the nucleus and could bind specifically to the promoter of PbrDHAR2 . PbrMYB5 was greatly induced by cold and salt but slightly by dehydration. Overexpression of PbrMYB5 in tobacco conferred enhanced tolerance to chilling stresses, whereas down‐regulation of PbrMYB5 in P. betulaefolia by virus‐induced gene silencing resulted in elevated chilling sensitivity. Transgenic tobacco exhibited higher expression levels of NtDHAR2 and accumulated larger amount of ascorbic acid (AsA) than the wild‐type plants. Virus‐induced gene silencing of PbrMYB5 in P. betulaefolia down‐regulated PbrDHAR2 abundance and decreased AsA level, accompanied by an increased sensitivity to the chilling stress. Taken together, these results demonstrated that PbrMYB5 was an activator of AsA biosynthesis and may play a positive role in chilling tolerance, at least in part, due to the modulation of AsA synthesis by regulating the PbrDHAR2 expression. Abstract : In this study, we isolated a novel R2R3‐type MYB transcription factor from Pyrus betulaefolia by yeast one‐hybrid screening, designated as PbrMYB5 . Transgenic tobacco exhibited higher expression levels of NtDHAR2 and accumulated larger amount of ascorbic acid (AsA) than the wild‐type plants. Our results demonstrated that PbrMYB5 was an activator of AsA biosynthesis and may play a positive role in chilling tolerance, at least in part, due to the modulation of AsA synthesis by regulating the PbrDHAR2 expression.